Diseño y construcción concentrador solar cilindro parabólico combinado con reflector solar de espejo plano. - Barrera Moreno, Cristian Ernesto; Vargas Fonseca, Gabriel Hernán (Universidad Antonio Nariño, 2022)
In this project, it seeks to study whether by combining two types of collectors in a compact way, energy production could be optimized; the collectors to be used are the parabolic trough and the flat mirror reflectors (Fresnel) in order to compare their efficiency between them and their behavior when combined.